LANGUAGE FUNCTION IN BAZ LUHRMANN’S MOVIE THE GREAT GATSBY - Sulaiman, Masagus; Marliasari, Sherly (Universitas Muhammadiyah Palembang, 2019)
This research is aimed at figuring out the dominant type of language function used by five characters in The great Gatsby movie directed by Baz Luhrmann.This research applied a descriptive-qualitative method. The researchers used Holmes and Hazen’s theory to analyze the data. The results showed 304 utterances of language function of 106 referential and 198 expressive utterances. The first character, Nick Carraway uttered 25 referential utterances and 61 expressive utterances. The second one, Jay Gatsby uttered 37 referential utterances and 57 expressive utterances. The third one, Daisy Fay Buchanan uttered 12 referential utterances and 35 expressive utterances.The fourth one, Tom Buchanan uttered 28 referential utterances and 42 expressive utterances, and the last one, Myrtle Wilson uttered 4 referential utterances and 3 expressive utterances. In conclusion, the dominant type of language function found was expressive utterance of 198 expressions which was greater than referential utterances of 106 expressions.